Performance evaluation of Indian electrical distribution utilities in the post Electricity Act 2003 era. (13th February 2012) - Saxena, Seema; Thakur, Tripta
Indian electricity sector constitutes a contrast a highly sophisticated modern generation and transmission system, but a very poor distribution system in several utilities. Despite the realisation of the importance of the distribution sector, the performances of Indian distribution utilities have not been measured empirically so far. The post Electricity Act 2003 (EA 2003) era has witnessed restructuring of power entities in India and the performance evaluation of the distribution sector is important in order to assess the impact of reform measures. Ministry of power (MoP) and the international funding agencies have also realised that it is vital for the success of any reforms programme to review the performance of existing utilities. Benchmarks and targets for improvement in performance can be identified by this analysis. This paper presents the measurement of technical efficiency for performance evaluation of electricity distribution utilities in India after the implementation of EA 2003. This study applies an engineering management tool data envelopment analysis (DEA) to assess the operating performance of Indian power distribution sector. The study includes only distribution companies (private as well as government owned) that existed on March 31, 2008 and covers all states and regions of the country.